Lung metastasis of endometrioid carcinoma aberrantly expressing thyroid transcription factor-1 - Mitsuhiro Tachibana; Masao Saito; Jun Kobayashi; Yutaka Tsutsumi (Elsevier, 2020)
It is known that thyroid transcription factor-1(TTF-1) is expressed in a small percentage of primary gynecological adenocarcinomas, including endometrial cancers. However, this is the first time this phenomenon has been reported that metastatic endometrioid carcinoma (EC) was induced TTF-1 by pulmonary niche. An 80'syear-old female patient, nonsmoker was addressed to our institution for the 14 mm solitary mass of the right lower lung. This tumor was negative for TTF-1. She had a previous history of grade2 EC of the uterine corpus. Chest computed tomography showed a 19 × 10 × 8- mm well-circumscribed lobular non-necrotizing mass. Right lower wedge resection was performed. Immunohistochemical findings showed that 20% of the neoplastic cells expressed TTF-1. In the present case, TTF-1 was expressed in the lung metastasis, but not in the primary EC of the uterus. Some lung factors might have induced TTF-1 in metastatic EC cells. The fact that TTF-1-positive cancer cells were located just adjacent to lung parenchyma suggests the influence of certain lung factors.